Pendidikan Islam Menyikapi Punishment Anak (Studi Literatur) - Mohammad Wisnu Khumaidi; Muhammad Ari Wibowo (ISLAM EDU : Jurnal Ilmiah Pendidikan Agama Islam, 2024)
Islam has regulated how to punish children when they make mistakes, namely: First, the basis for treating children is in a gentle and loving way, as stated in the following Hadith: Al-Bukhari stated in Al-Adabul Mufrad, "Be gentle and stay away from violence and abomination." Second, pay attention to the child's character when deviating and then apply punishment. In this context, what needs to be considered is that every human child has different intelligence and temperament with diverse family life background conditions. The Prophet (peace and blessings of Allaah be upon him) has given instructions: 1. Showing mistakes with direct direction. 2. Pointing out mistakes in a polite and kind way. 3. Indicating an error with a signal. Punishment is one of the tools used in Islamic education to return wrong deeds to the right path. But its use must not be arbitrary, especially in corporal punishment, it must follow existing provisions. Delaying punishment has a greater effect than punishing it outright. This delay will prevent him from repeating another mistake for fear of getting two punishments. Of course, this kind of action should not be carried out continuously. If we have tried to educate them in other ways and it turns out that we are not willing to obey, then the last alternative is physical punishment. The educational leaders provided the stages of sentencing to be effective and effective, namely: First, giving advice in the right way and at the right time. Second, the punishment of neglect, to foster feelings of discomfort and neglect in the hearts of children. Third, physical punishment, as the final stage, with the note that the physical punishment (blow) given is not too harsh and painful. The ways that Islam takes in punishing children are: 1. treating children gently and affectionately, 2. paying attention to the child's deviant character when applying punishment, 3. finding solutions gradually, starting from light ways and switching to heavy ones. The purpose of punishment in Islamic education is to improve the character and behavior of students to educate children in the direction of ignorance so that they will not repeat the same mistakes and take responsibility for their mistakes.